Subacute and long-term effects of COVID-19 on cardiac health and function in German elite athletes assessed by strain analysis: a speckle tracking echocardiography observational trial - Zacher, J.; Joisten, N.; Schmidt, T.; Predel, H.-G. (Sport Sciences for Health, 2024)
Introduction During the COVID-19-pandemic, most elite athletes were infected with the novel severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Initial worries of high rates of multi-organ complications including the heart and ending sporting careers were disproved by large studies. However, the effects of COVID-19 on the heart and its function in elite athletes remains unclear, especially in the prolonged post-infection follow-up and during and after return to competition.